Analisis pengaruh upah minimum, belanja pemerintah dan pendapatan asli daerah terhadap tingkat kemiskinan pada provinsi mayoritas muslim - Utami, Indah Tri; Rofiuddin, Mohammad (Journal of Economics Research and Policy Studies, 2022)
This study aims to determine the effect of the Minimum Wage, Government Expenditure and Regional Original Income on poverty in the province with the largest Muslim majority population in Indonesia. The objects of this research are 10 provinces with the largest Muslim majority population in Indonesia in 2017-2020. The method used to see the effect of using panel data regression is the Fixed Effect Model. The results of this study indicate that simultaneously Minimum Wage, Government Expenditures and Regional Original Income have an effect on poverty in the province with the largest Muslim majority population in Indonesia. The Minimum Wage has no effect on poverty in the Province with the largest Muslim majority population in Indonesia, while Government Expenditures and Regional Original Income reduce poverty in the Province with the largest Muslim majority population in Indonesia. This research model clarifies the role of Government Expenditures and Regional Original Income in poverty alleviation in the province with the largest Muslim majority population in Indonesia.